2020
DOI: 10.1002/hbm.25099
|View full text |Cite
|
Sign up to set email alerts
|

The developmental neural substrates of Hebb repetition learning and their link with reading ability

Abstract: Hebb repetition learning is a fundamental learning mechanism for sequential knowledge, such as language. However, still little is known about its development. This fMRI study examined the developmental neural substrates of Hebb repetition learning and its relation with reading abilities in a group of 49 children aged from 6 to 12 years. In the scanner, the children carried out an immediate serial recall task for syllable sequences of which some sequences were repeated several times over the course of the sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…While some studies observed a role for the hippocampus in the maintenance of temporal sequences (Fortin et al 2002;Hsieh et al 2014;Jenkins and Ranganath 2016;Roberts et al 2018), other studies did not observe a specific response to serial order information in this area (Majerus et al 2006(Majerus et al , 2010Papagno et al 2017;Attout et al 2019). Many studies reporting hippocampal involvement in ordinal processing used tasks that had also a consolidation and long-term memory component such as in Hebb learning paradigms (Kalm et al 2013;Attout et al 2020). The hippocampus may support episodic memory for ordinal information rather than ordinal information per se.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies observed a role for the hippocampus in the maintenance of temporal sequences (Fortin et al 2002;Hsieh et al 2014;Jenkins and Ranganath 2016;Roberts et al 2018), other studies did not observe a specific response to serial order information in this area (Majerus et al 2006(Majerus et al , 2010Papagno et al 2017;Attout et al 2019). Many studies reporting hippocampal involvement in ordinal processing used tasks that had also a consolidation and long-term memory component such as in Hebb learning paradigms (Kalm et al 2013;Attout et al 2020). The hippocampus may support episodic memory for ordinal information rather than ordinal information per se.…”
Section: Discussionmentioning
confidence: 99%
“…However, this same explanation might not explain the opposite age effects observed with the Hebb task because unlike performance on the SRT, performance on the Hebb task has not been strongly associated with procedural learning (Nicolson and Fawcett, 2007). In fact, the Hebb task has been associated with modulation of brain regions such as the hippocampus, cingulate cortex and inferior frontal cortex (Attout et al, 2020), making it more likely to be a form of declarative memory or potentially relying on working memory rather than procedural memory. Thus, a greater Hebb learning impairment in adults rather than children with dyslexia doesn't seem to be explained well by a compensatory mechanism of declarative memory.…”
Section: Age Effectsmentioning
confidence: 98%
“…Over the past decades, repetition learning has often been considered an example for an implicit learning process, that is, people don't have to be aware that they are encoding the same information over and over again for building up a long-term memory representation (Attout et al, 2020;Couture & Tremblay, 2006;Guérard et al, 2011;Hebb, 1961;McKelvie, 1987). Yet, mechanistic explanations of repetition learning have agreed that some form of recognition mechanism is required to ensure that longterm memory representation of previous experiences are used only, when a sufficient overlap between a previous and a new encounter of the same information is detected (Burgess & Hitch, 2005, 2006Page & Norris, 2009).…”
Section: The Role Of Awareness In Repetition Learning and Chunk Forma...mentioning
confidence: 99%